The Influence of Women's Economic Empowerment on Technology Entrepreneurship Intention Through Self-Efficacy in Womenpreneurs in Surabaya - Gabriel Carolina Tjoe; Mohamad Trio Febriyantoro (Institute of Computer Science (IOCS), 2026)
This study investigates the influence of Women Economic Empowerment on Technology Entrepreneurship Intention through the mediating role of Self-Efficacy among womenpreneurs in Surabaya, Indonesia. This study aims to examine whether the WEE-SE-TEI framework, originally developed in a Middle Eastern context, holds in a Southeast Asian setting. A quantitative survey approach was employed. Data were collected from 120 female entrepreneurs in Surabaya using purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results confirm that Women Economic Empowerment positively and significantly influences both Self-Efficacy and Technology Entrepreneurship Intention, and that Self-Efficacy partially mediates this relationship. Future research should extend this framework to broader geographic contexts and incorporate additional variables such as digital literacy and social capital